Alcaloides de annonacea: ocorrência e compilação de suas atividades biológicas e avaliação fitoquímica e biológica de Anaxagorea dolichocarpa Sprague & Sandwith (Annonaceae) - Lúcio, Ana Silvia Suassuna Carneiro (2015)
This work consists of four chapters. The Chapter 1 describes a review of all alkaloids reported in the literature for the Annonaceae family, with its botanical occurrence and biological activities. 934 alkaloids have been reported in publications in the period from 1929 to 2012. Chapter 2 this is the isolation and identification of alkaloids Annonaceae family species, Anaxagorea dolichocarpa. By chromatographic and spectroscopic methods could be the isolation and identification of azaphenanthrenes alkaloids: eupolauramine, sampangine and imbiline 1 already reported to Anaxagorea dolichocarpa, the roots being reported for the first time, the 3- metoxisampangina alkaloid first isolated Anaxagorea dolichocarpa and the alkaloid Imbiline 4, first reported in the literature. The Chapter 3 reports the pharmacological studies on activities antitumor, Leishmanial and immunomodulatory of the isolated alkaloids. The imbiline 1 stood out by presenting significant antitumor activity and was also effective in immunomodulatory activity against inhibition of nitric oxide production. For Leishmanial activity, all substances were active, especially the sampangine. Chapter 4 refers to a theoretical study of the reported aporphines alkaloids in the review of published alkaloids Annonaceae and azaphenanthrenes of Annonaceae alkaloids. The study was performed by machine learning using molecular docking and molecular descriptors for Leishmanial activity.